2015
DOI: 10.1111/cyt.12280
|View full text |Cite
|
Sign up to set email alerts
|

Age cut-off for reporting endometrial cells on a Papanicolaou test: 50 years may be more appropriate than 45 years

Abstract: In asymptomatic women less than 50 years, E40 correlated with benign, non-hyperplastic endometrium. However, post-menopausal women with E40 had a risk of EC. Perhaps endometrial cells should only be reported in post-menopausal women or women greater than or equal to 50 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…Our data indicates that there is no benefit to report EMCs below 50 years of age, in fact reporting EMCs only in postmenopausal women seems to be a reasonable alternative. Setting the cut‐off age for reporting to ≥50 has been supported by other authors and this is also close to the average age of menopause. Although many factors (racial/ethnic and socioeconomic differences, diet, environmental influences, and physical activity) have some effect on it, the average age of menopause is approximately 51 years in the well‐developed industrialized countries .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our data indicates that there is no benefit to report EMCs below 50 years of age, in fact reporting EMCs only in postmenopausal women seems to be a reasonable alternative. Setting the cut‐off age for reporting to ≥50 has been supported by other authors and this is also close to the average age of menopause. Although many factors (racial/ethnic and socioeconomic differences, diet, environmental influences, and physical activity) have some effect on it, the average age of menopause is approximately 51 years in the well‐developed industrialized countries .…”
Section: Discussionsupporting
confidence: 65%
“…While most publications understandably focus on the ideal age of reporting EMCs, our findings suggest that reporting EMCs in postmenopausal women would be just as efficient, but it requires consistent reporting of the menopausal status and LMP. The inclusion of risk factors (diabetes, postmenopausal status, strong family history of breast, and endometrial cancers) in the reporting guidelines for EMCs as suggested by other authors would also require reliable clinical information on the requisitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 63 cases of EC that were identified, only 1 (1.6%) had BECs on Pap test, and this patient developed EC at the age of 51 years. Many other groups have also produced similar results in various patient clinical settings [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 69%
“…[13] reported that BECs on Pap tests and subsequent endometrial sampling leads to the detection of underlying EC in women (regardless of the menstrual cycle) ≥ 50 years old. Researchers from Vanderbilt found that only 1.4% of BECs are associated with ECs in patients over the age of 50 years [14] . This group also gathered all endometrial cancer cases and back-tracked the prior Pap test.…”
Section: Discussionmentioning
confidence: 99%